The Life of John Milton, Volume 5 (of 7), 1654-1660 : Narrated in Connexion with the Political, Ecclesiastical, and Literary History of His Time - Masson, David, 1822-1907 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Life of John Milton, Volume 5 (of 7), 1654-1660" by David Masson is a historical account written in the late 19th century. This volume delves into a crucial period of English history during Oliver Cromwell's Protectorate, focusing on John Milton's role as a Latin Secretary and his interactions with the political and ecclesiastical dynamics of the time. The narrative captures the turbulent political landscape following the English Civil War, highlighting debates surrounding governance, religious tolerance, and the rise of various dissenting sects. The opening of the volume sets the stage for a detailed exploration of Cromwell's first Parliament from September 1654 to June 1657, emphasizing the complexities of governance during this period. It outlines the composition of Parliament and the challenges Cromwell faced from both Oliverians and Anti-Oliverians. Included are discussions on significant issues like the limitations of Cromwell's powers, the politics surrounding religious toleration, and the emergence of new religious sects, such as the Quakers and Fifth Monarchy Men. This account promises a rich examination of how Milton navigated his intellectual and political responsibilities amid a rapidly changing socio-political environment. (This is an automatically generated summary.)
Release date is 2004-12-19
E-text prepared by Charles Aldarondo, Keron Vergon, Leonard Johnson, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Poets, English -- Early modern, 1500-1700 -- Biography; Milton, John, 1608-1674